2021
DOI: 10.3390/ijms222111695
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ghrelin Dynamics in Stress-Induced Eating Disorder: Effects of Sex and Aging

Abstract: Stress, a factor that affects appetite in our daily lives, enhances or suppresses appetite and changes palatability. However, so far, the mechanisms underlying the link between stress and eating have not been fully elucidated. Among the peripherally produced appetite-related peptides, ghrelin is the only orexigenic peptide, and abnormalities in the dynamics and reactivity of this peptide are involved in appetite abnormalities in various diseases and psychological states. This review presents an overview of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 124 publications
0
4
0
2
Order By: Relevance
“…In the already-mentioned Korean study ( Baek et al , 2018 ), 36 out of 142 patients with BE (25%) were men compared with 22% in the overall sample. In the last few years, research has shed more light on the role of sex in EDs, pointing to differences in stress hormones and the ghrelin system ( Yamada, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the already-mentioned Korean study ( Baek et al , 2018 ), 36 out of 142 patients with BE (25%) were men compared with 22% in the overall sample. In the last few years, research has shed more light on the role of sex in EDs, pointing to differences in stress hormones and the ghrelin system ( Yamada, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[6] reported that the GHRL gene SNPs contributed with many genetic factors to create genetic variation in carcass quality in beef cattle while [7] mentioned that the gene is considered one of candidate genes for milk production traits in water buffalo. [8] referred that the gene polymorphism plays an important role to enhance stress tolerance and support appetite under stress conditions. The major aim of the current study is to investigate of single nucleotide polymorphism effect in GHRL gene on milk production and components as an efficient method of indirect selection or markers assisted selection in dairy herds).…”
Section: Introductionmentioning
confidence: 99%
“…Стресові фактори можуть впливати на апетит, рухову активність шлунково-кишкового тракту і функцію травлення. Фізіологічна реакція на стрес різниться залежно від того, чи є стрес гострим, чи хронічним [8,9] Гострий стрес зазвичай вважається адаптивним механізмом організму, але хронічний стрес може викликати різні порушення біологічних функцій. Деякі фактори впливають на реакцію апетиту на стресори у парадоксальний спосіб.…”
unclassified